“People will choose for you”: : Corporate social advocacy controversies as a window into the contemporary promotional industries - Hill, Stephanie (Comunicação Mídia e Consumo, 2023)
Amid calls for more impactful corporate social responsibility and the growing significance of corporations and brands as sites to contest societal values, this article asks how a changed communication environment affects the practices of organisational communication, and with what effects? Through a thematic analysis of interviews, observation at industry events, and collected documents, it examines the motivations for corporate social advocacy, their mediation, and how the risks and rewards of participating in these kinds of communication are understood within the contemporary promotional industries. Using frameworks of contestation and justification, it identifies how constant media scrutiny, a low-trust environment, and investments in stakeholder relationships exacerbated the risks and rewards of social advocacy, pushing corporate advocacy towards tangible actions with governance implications.